Distribution of the ixodid tick Hyalomma marginatum Koch (Acari: Ixodidae) in the Stavropol region - Boris Konstantinovich Kotti; Irina Nikolaevna Zaikina; Maria Vladimirovna Zhiltsova (Наука. Инновации. Технологии)
Distribution of ixodid ticks, as well as other temporary ectoparasites, is determined by the location of their hosts and abiotic factors. One of the numerous species of iхodid ticks in Ciscaucasia is Hyalomma marginatum Koch - an active carrier of the Crimean haemor-rhagic fever. In the territory of Stavropol Region there is a favourable environment for the habitation of this species. At the same time, in each landscape province, the thermal conditions and the number of hosts of the imago are very different, which affects the survival, development and abundance of this species. H. marginatum is found around the Stavropol Region, preferring semi-desert, steppe and meadow habitats. Hosts of imagoes of H. marginatum in the Stavropol region is, mainly, cattle. The greatest importance as hosts of larvae and nymphs are abundant species of birds feeding on the ground, hare and hedgehogs. The number of ticks increases from mountainous to semi-desert landscapes where it is widespread and is the dominant species.